Antitumour and antiangiogenic effects of IDN 5390, a novel C-seco taxane, in a paclitaxel-resistant human ovarian tumour xenograft - Petrangolini, G (Nature Publishing Group, 2004)
IDN 5390 is a novel C-seco taxane analogue selected for preclinical development on the basis of its antimotility activity on endothelial cells, antitumour efficacy in a large panel of human tumour xenografts and high tolerability in mouse. On the basis of oral availability, IDN 5390 is suitable for protracted administration schedules. Such a treatment schedule has been reported as the most appropriate to exploit the antiangiogenic effects of cytotoxic drugs. An ability to downregulate angiogenesis-related growth factors in tumour cells has been described for IDN 5390. The aim of the study was to investigate the antitumour and antiangiogenic potential of oral IDN 5390 on a human ovarian carcinoma xenograft, the INT.ACP/PTX, resistant to paclitaxel (PTX). Such tumour line was derived in vivo from a cisplatin-resistant tumour line, the A2780/DDP, which is sensitive to PTX. Compared to the parental cells, INT.ACP/PTX cells exhibited a high level of Pgp expression, resulting in a reduced in vitro sensitivity to both PTX and IDN 5390. The INT.ACP/PTX tumour xenograft was still resistant to PTX, but responsive to IDN 5390, when delivered per os, by a daily prolonged schedule. A direct effect on tumour cells, allowed by the high tolerability of the compound in mouse, cannot be excluded in vivo. Immunohistochemical analysis indicated a significant reduction of microvessel density in IDN 5390-treated tumours, lasting till 7 days after the last drug administration. Thus, a prolonged inhibitory effect on tumour angiogenesis is consistent with the persistent growth control of INT.ACP/PTX tumour achieved by IDN 5390. On the contrary, the low tolerability and the limited oral availability of conventional taxanes do not allow an easy feasibility of such treatment regimen. Thus, the tolerability profile of IDN 5390 in preclinical systems and its efficacy in PTX-resistant tumours support the therapeutic interest for its clinical development, with particular attention to oral daily prolonged schedules.